“KAMPUNG VERTICAL” DESIGN IN URBAN VILLAGE AS URBAN RENEWAL STRATEGY (CASE STUDY: GANDEKAN VILLAGE, SEMARANG) - Darmawan, Edy; Lubis, M. Ikhsan Maulana (Department of Architecture, Institut Teknologi Sepuluh Nopember (ITS), 2023)
Urbanization or the movement of people from villages to cities has caused many problems, both socio-economic, environment, and illegal housing which is carelessly constructed due to the increasing need for housing. To overcome this situation, urban renewal can be an effective solution. This urban renewal focuses on the presence of vertical housing as a realignment of the residential housing design for community. It focuses on the presence of a space that protects the environment, the health of residents, and accommodatesthe activities of its community. Vertical villages are familiarin Indonesia, especially in urban village areas that were shabby. Therefore, this research purposed for the designing of a vertical village in Gandekan Village area of Semarang. Due to the growth of the population and the increasingly advanced of Semarang City, many villagers moved in to obtain a more decent job, but problems were also arising in this phenomenon.